Eyes grow towards mild hyperopia rather than emmetropia in Chinese preschool children. Issue 8 (3rd May 2021) - Ma, Yingyan; Lin, Senlin; Morgan, Ian G.; Rozema, Jos J.; Iribarren, Rafael; Zhu, Jianfeng; Zhao, Rong; Zhang, Bo; Yin, Yao; Shao, Yueqin; He, Xiangui; Xu, Xun; et al.
Abstract: Purpose: To document one‐year changes in refraction and refractive components in preschool children. Methods: Children, 3– 5  years old, in the Jiading District, Shanghai, were followed for one year. At each visit, axial length (AL), refraction under cycloplegia (1% cyclopentolate), spherical dioptres (DS), cylinder dioptres (DC), spherical equivalent refraction (SER) and corneal curvature radius (CR) were measured. Results: The study included 458 right eyes of 458 children. The mean changes in DS, DC and SER were 0.02 ± 0.35 D, −0.02 ± 0.33 D and 0.01 ± 0.37 D, while the mean changes in AL, CR and lens power (LP) were 0.27 ± 0.10 mm, 0.00 ± 0.04 mm and − 0.93 ± 0.49 D. The change in the SER was linearly correlated with the baseline SER (coefficient = −0.147, p < 0.001). When the baseline SER was at 1.05 D (95% CI = 0.21 to 2.16), the change in SER was 0 D. The baseline SER was also linearly associated with the change in LP (coefficient = 0.104, p = 0.013), but not with the change in AL (p = 0.957) or with the change in CR (p = 0.263). Conclusion: In eyes with a baseline SER less than +1.00 D, LP loss was higher compared to axial elongation, leading to hyperopic shifts in refraction, whereas for those with baseline SER over this range, loss of LP compared to axial elongation was reduced, leading to myopic shifts. This model indicated the homeostasis of human refraction and explained how refractive development leads to a preferred state of mild hyperopia.